The preoperative and the postoperative neutrophil-to-lymphocyte ratios both predict prognosis in gastric cancer patients - Kim, Eun Young (World J Surg Oncol, 2020)
BACKGROUND: Both the preoperative and postoperative neutrophil-to-lymphocyte ratios (NLRs) have been proposed to predict the long-term prognosis in some cancers, including gastric cancer. The present study investigated the prognostic impact of postoperative NLR, and its preoperative to postoperative changes, in patients with gastric cancer. METHODS: From 2009 to 2012, 1227 consecutive patients who underwent curative surgery for gastric cancer were enrolled in this study. The optimal cut-off value for the postoperative 6-month NLR was 1.7, as determined by receiver operating characteristic curve analysis. Patients were categorized into low- and high-NLR groups based on their postoperative NLR. Four additional groups (low to low, low to high, high to low, and high to high groups) were defined based on the preoperative to postoperative change in the NLR. RESULTS: The 5-year overall survival (OS) rates of the low- and high-NLR group were 90.7% and 83.0%, respectively (P < 0.001). The differences in OS were significant in stage I and stage III gastric cancer patients (P< 0.001 and 0.012, respectively). Postoperative NLR was an independent prognostic factor for OS (hazard ratio [HR] = 1.556; P = 0.010). The high to high NLR change was a significant predictor of OS (HR = 1.817; P = 0.003). CONCLUSIONS: High preoperative and postoperative NLRs, and especially the persistent elevation of preoperative to postoperative NLR, were significant poor prognostic factors for OS in patients with gastric cancer. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s12957-020-02059-4.